Geochemistry and ore potential of the Almoughlagh batholith, western Iran - Zamanian, Hassan; Asadollahi, Behrooz (Geologos, 2013)
The Almoughlagh batholith intruded the dioritic Baba Ali pluton during the Oligo-Miocene; the pluton and is now exposed as a big enclave within the batholith. The pluton intruded the Songhor Series during the Late Kimmeridgian ( 136 Ma) orogeny. The intrusion by the batholith transformed the diorite to metadiorite and the impure carbonate units of the Songhor Series. The batholith consists of rock types such as quartz syenite and syenogranite, which have a low average quartz content, and which are metaluminous to peraluminous and calc-alkaline in composition. Comparison of the compositions of the Almoughlagh batholith and the pluton with its Cu, Mo, Fe, Sn, W, Au, and Zn skarn deposits, indicates that the Baba Ali diorite geochemically shows much resemblance with those which could bring about Fe-Cu skarn mineralization, whereas the compositions of the Almoughlagh granitoids resembles those of the plutons associated with Mo and Zn skarn deposits. The associated hydrothermal activity related to the Almoughlagh batholith culminated in magnetite mineralisation in the Baba Ali and the Chenar mines in which copper mineralisation also is considerable.